AC breakdown behavior of SF6/N2 gas mixtures under non-uniform field electrode configurations - N. F. Ambo; H. Zainuddin; M. S. Kamarudin; J. M. Wari; A. Zahari (Universitas Ahmad Dahlan, 2019)
Sulphur hexafluoride (SF6) gas owns remarkable properties as insulation medium and current interrupter, which make it being widely used in gas-insulated equipment up to now. However, SF6 gas has a drawback that gives adverse effect to the environment since it is a strong greenhouse gas. As the effort to minimize the SF6 usage, this study was conducted to investigate the AC breakdown behavior of SF6/N2 gas mixtures with 10/90 ratio at low pressure levels (i.e. 0.11 MPa to 0.15 MPa) under non uniform field (i.e. R0.5-plane and R6-plane electrodes configurations). The results of the study indicate that the breakdown voltage of SF6/N2 gas mixtures in non-uniform field increases linearly with the increase of gas pressure and electrodes gap distance. As a function of gap distance, a higher increasing rate of breakdown voltage values were achieved at lowest pressure of 0.11 MPa compared to other pressure levels. In addition, it is also found that a higher breakdown voltage values was obtained under R6-plane configuration. But, the difference in breakdown voltage values between R0.5-plane and R6-plane configuration is less significant as the gap distance is increased. It is also observed that the field efficiency factor of R6-plane is higher than R0.5-plane which indicates a more uniform field exists between the electrodes.